REPRESENTASI MATEMATIS TERHADAP PEMAHAMAN KONSEP PECAHAN DESIMAL DITINJAU DARI PERBEDAAN GENDER PADA SISWA SD NEGERI BLANG BINTANG - Rahmayani, Suri; Isa, Muhammad; Suryawati, Indah (Jurnal Seramoe Education, 2024)
Representation is a student’s ability to communicate mathematical ideas or ideas that are learned in a certain way. The formulation of the problem in this research is whether or not there are differences in mathematical representation in understanding the concept of decimal fractions in terms of gender differences in fourth grade students at SD Negeri Blang Bintang. This research aims to find out how mathematical representation influences the understanding of the concept of decimal fractions for male and female students. The subjects in this research were grade IV elementary school students at Blang Bintang State Elementary School. This research uses a quantitative comparative approach, in other words the researcher compares one another. The population in this study were all fourth grade students at SD Negeri Blang Bintang consisting of one class with a total of 24 students. Sampling was carried out using a purposive sampling technique, selected from 24 students, namely 11 male students and 11 female students, 2 students still took the test but their scores were not included. The data collection technique is in the form of giving tests to students, namely pre-test and post-test. Data was taken through the independent samples t-test with significance analysis using SPSS 24. After the normality test was carried out, it can be concluded that the results of the independent samples t-test calculation show where the sig value. (2-tailed) the average N-Gain score for the ability to understand the mathematical representation of decimal fractions is 0.617 greater than 0.05 with the criterion tcount > ttable so that the null hypothesis (H0) is accepted and the alternative hypothesis (Ha) is rejected. Based on the decision criteria provided determined, it can be stated that the mathematical representation of understanding the concept of decimal fractions is that there is no difference between male and female students in class IV of SD Negeri Blang Bintang.